Analysis of Factors Affecting the Production of Rice Farming in Lampuara Village, South Ponrang District, Luwu Regency - Misra Indarsari; Syafruddin Syafruddin; Adi Rianto Suprayitno (Journal of Global Sustainable Agriculture, 2024)
This research analyzes the factors that influence rice production in Lampuara Village, South Ponrang District, Luwu Regency, South Sulawesi Province, Indonesia. The factors studied include farmer characteristics, agricultural management and agricultural expansion. This research aims to evaluate the directness and influence of these factors indirectly affecting the production of rice farming. The research method uses descriptive analysis techniques using the SPSS application and inferential analysis using a variant-based Structural Equation Model (SEM) or VB-SEM. The research results show that having farmer characteristics, such as land area, business experience and level of education, has a significant direct impact on production. paddy. Even though agricultural business management has a relatively small impact, it is still important for agricultural efficiency and sustainability. Agricultural extension also plays an important role in increasing production, which involves several factors such as frequency of extension, appropriateness of materials, media and methods contributing to supporting increased rice production. This research highlights the complexity of the relationship between farmer characteristics, agricultural management and agricultural extension in the local agricultural context. The practical implications of this research include the importance of considering farmer education, optimizing agricultural holding management and improving the quality of expansion to achieve increased agricultural rice production. Regular monitoring and evaluation is also needed, identifying changes in these factors and adapting strategies according to the conditions and needs of farming communities. This research provides valuable insights for agricultural extension workers, farmers and stakeholders in local agricultural development to achieve better agricultural results and farmer welfare.